Transformation of Air Quality over a Coastal Tropical Station Chennai during COVID-19 Lockdown in India - Jyotsna Singh; Bhishma Tyagi (Aerosol and Air Quality Research)
Abstract To prevent the spread of COVID-19, Government of India imposed strict lockdown in the country from 24 March–31 May 2020, which allows the environment to revive with reduced emissions. The present work analyses the PM2.5, NO2, O3, CO and SO2 along with meteorological parameters (humidity, temperature and wind speed) at a tropical coastal station Chennai for March-May 2019 and 2020 at five locations: Alandur Bus depot, Velachery, Manali, Teynampet and U.S. Embassy Chennai. Chennai is a megacity of southern India and the state capital of Tamil Nadu, one of the worst affected states due to COVID-19. Though overall PM2.5 values decreased for the lockdown (ranging from ~32–187%), weekly analysis shows the variation in reduction/increase. SO2 and O3 values were found increasing for two sites: Teynampet (~40% in SO2 and ~48% in O3) and Velachery (~42% in SO2 and ~5% in O3), but decreasing for Alandur (~30% in SO2 and ~50% in O3) and Manali (~247% in SO2). NOx and CO were reduced during the lockdown (~47–125%) for all the sites. The source regions examined by concentration weighted trajectory analysis were found to change for transporting pollution to the site. The analysis shows there are local scale variations in the air pollution for the city during COVID-19 lockdown.